Reduced Morbidity and Mortality in Survivors of Childhood Acute Lymphoblastic Leukemia: A Report From the Childhood Cancer Survivor Study - Dixon, Stephanie B; Chen, Yan; Yasui, Yutaka; Pui, Ching-Hon; Hunger, Stephen P; Silverman, Lewis B; Ness, Kirsten K; Green, Daniel M; Howell, Rebecca M; Leisenring, Wendy M; Kadan-Lottick, Nina S; Krull, Kevin R; et al. (Journal of clinical oncology, 2020)
Risk-stratified therapy, which modifies treatment on the basis of clinical and biologic features, has improved 5-year overall survival of childhood acute lymphoblastic leukemia (ALL) to 90%, but its impact on long-term toxicity remains unknown. We assessed all-cause and health-related late mortality (including late effects of cancer therapy), subsequent malignant neoplasms (SMNs), chronic health conditions, and neurocognitive outcomes among 6,148 survivors of childhood ALL (median age, 27.9 years; range, 5.9-61.9 years) diagnosed between 1970 and 1999. Therapy combinations and treatment intensity defined 6 groups: 1970s-like (70s), standard- or high-risk 1980s-like (80sSR, 80sHR) and 1990s-like (90sSR, 90sHR), and relapse/transplantation (R/BMT). Cumulative incidence, standardized mortality ratios, and standardized incidence ratios were compared between treatment groups and with the US population. Overall, 20-year all-cause late mortality was 6.6% (95% CI, 6.0 to 7.1). Compared with 70s, 90sSR and 90sHR experienced lower health-related late mortality (rate ratio [95% CI]: 90sSR, 0.2 [0.1 to 0.4]; 90sHR, 0.3 [0.1 to 0.7]), comparable to the US population (standardized mortality ratio [95% CI]: 90sSR, 1.3 [0.8 to 2.0]; 90sHR, 1.7 [0.7 to 3.5]). Compared with 70s, 90sSR had a lower rate of SMN (rate ratio [95% CI], 0.3 [0.1 to 0.6]) that was not different from that of the US population (standardized incidence ratio [95% CI], 1.0 [0.6 to 1.6]). The 90sSR group had fewer severe chronic health conditions than the 70s (20-year cumulative incidence [95% CI], 11.0% [9.7% to 12.3%] 22.5% [19.4% to 25.5%]) and a lower prevalence of impaired memory (prevalence ratio [95% CI], 0.7 [0.6 to 0.9]) and task efficiency (0.5 [0.4 to 0.7]). Risk-stratified therapy has reduced late morbidity and mortality among contemporary survivors of standard-risk ALL, represented by 90sSR. Health-related late mortality and SMN risks among 5-year survivors of contemporary, standard-risk childhood ALL are comparable to the general population.